Islamic finance the regulatory challenge - Archer, Simon; Abdel Karim, Rifaat Ahmed (J. Wiley & Sons (Asia), 2007)
Islamic Finance: The Regulatory Challenge...is therefore timely and a truly welcome addition to the growing literature on this subject...I congratulate the two professors for their fine contribution to the evolving art and science of the regulation of Islamic finance.